Sweetpotato seed systems: A question of quantity and quality - International Potato Center (2012)
Research breakthroughs to lower the cost of maintaining disease-free planting material and to help farmers in drought-prone areas produce vines for the beginning of the rains may truly help break the bottleneck of timely access to planting material.